The Influence of Organizational Culture on Turnover Intention with Green Human Resource Management as an Intervening Variable in Generation Z Employees in Sleman Regency - Kholidi, Silma Luthfiatul; Wening, Nur (Golden Ratio of Data in Summary, 2025)
This research aimed to analyze the influence of organizational culture on turnover intention with green human resource management as an intervening variable. The population in this research consisted of Generation Z employees in Sleman Regency. The sampling method employed was purposive sampling, resulting in 100 respondents who met specific criteria, namely Generation Z employees in Sleman Regency aged 18-28 years. Primary data were collected through questionnaires that had been tested for validity and reliability. The data analysis in this study revealed both direct and indirect effects. The data analysis methods used in this research were classical assumption tests, path analysis, and hypothesis testing. The results of the data analysis indicated that: (1) Organizational culture has a positive and significant effect on green human resource management, (2) Green human resource management has a negative and significant effect on turnover intention, (3) Organizational culture has a negative and significant effect on turnover intention, (4) There is no mediating role of green human resource management in the relationship between organizational culture and turnover intention.